2006
DOI: 10.1186/1478-7954-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and urbanization in the Omani population: an analysis of national survey data

Abstract: Background: The prevalence of type 2 diabetes in Oman is high and appears to be rising. Rising rates of diabetes and associated risk factors have been observed in populations undergoing epidemiological transition and urbanization. A previous study in Oman indicated that urbandwellers were not significantly more likely to have diabetes. This study was undertaken to determine if a more accurate urban and rural categorization would reveal different findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 19 publications
(14 reference statements)
2
72
0
Order By: Relevance
“…Interestingly, this prevalence is considerably lower than that for other ethnicities (48% in Sunni Arabs and 31% in Jafari Arabs) but is nevertheless much higher than what was observed in our study (9). The overall prevalence of diabetes in Oman, another neighboring country, was reported as 11.6% in 2000 (10). That study also noted much higher diabetes prevalence in the urban population (17.7%) compared with the rural population (10.5%).…”
mentioning
confidence: 34%
“…Interestingly, this prevalence is considerably lower than that for other ethnicities (48% in Sunni Arabs and 31% in Jafari Arabs) but is nevertheless much higher than what was observed in our study (9). The overall prevalence of diabetes in Oman, another neighboring country, was reported as 11.6% in 2000 (10). That study also noted much higher diabetes prevalence in the urban population (17.7%) compared with the rural population (10.5%).…”
mentioning
confidence: 34%
“…A number of recent studies have focused on the associations between urbanization levels and incidences of disease, such as diabetes, breast cancer, allergic diseases, and asthma, with the results showing that urbanization had significant impacts on the prevalence rates of various diseases. [27][28][29][30] We believe, however, that this nationwide population-based study represents the first of its kind to attempt to examine the association between the level of urbanization and the prevalence of strokes.…”
Section: Discussionmentioning
confidence: 98%
“…A 4-kg weight loss significantly reduces the risk of glycaemic decline early in the course of diabetes [25]. Hypertensives (60%) and obesity (26.4%) among adults with T2DM led to poorly controlled HbA1C (67%) [30,31,11]. Those with poor glycemic control are more likely to have hypertension than those well-controlled [25].…”
Section: Discussionmentioning
confidence: 99%
“…More than 14% of Oman populations with T2DM had diabetic retinopathy, 27% had microalbuminuria and 50% had amputations in Oman compared to 11.6% of Saudis and 6.7% of Indians with retinopathy [8,9]. Among 7442 Type 1 DM and T2DM patients, only 22.8% had good glycemic control influenced by control of blood pressure, blood glucose and body mass index, while 77.2% did not have a good glycemic control [10,11]. Among 5000 adults with DM, it was found that smoking, insulin and waist-hip ratio influenced the control of HbA1C [12,4].…”
Section: Introductionmentioning
confidence: 99%